Experimental study based on the usage of polymers for greywater treatment - Soussa, Hoda Kamal; Ahmed, Mostafa E.Y.; Taha, Moawad M.; Nabil Ali, Mohamed (Journal of Degraded and Mining Lands Management, 2024)
Water scarcity presents a pressing challenge in Egypt, exacerbated by factors such as population growth, urbanization, and climate change impacts. With over 95% reliance on the Nile River for freshwater supply, Egypt's water resources are strained, particularly with a population exceeding 100 million. Egypt's arid climate intensifies water scarcity, necessitating sustainable management strategies. This study explored greywater treatment as a solution to alleviate water scarcity in Egypt, investigating its technical feasibility, economic viability, and environmental benefits. Greywater, derived from domestic activities, is an underutilized resource that can be reclaimed and treated for reuse, reducing demand for freshwater sources. Through greywater treatment systems, households and communities can recycle water, conserve resources, and mitigate pollution. The study investigated using polymers as a coagulant in greywater treatment, examining its efficacy in removing contaminants and improving water quality. Experimental trials were conducted to evaluate the performance of polymer addition in greywater treatment compared to conventional methods. Results demonstrate that polymer addition reduces turbidity, suspended solids, and organic pollutants in greywater. Poly aluminum chloride (PAC) polymer, in particular, exhibits strong coagulation capabilities, versatility across pH ranges, and high efficiency in contaminant removal. Additionally, PAC offers operational advantages such as low dosage requirements and reduced sludge production.